Femtoscopy of the Origin of the Nucleon Mass - Krein, G. [UNESP]; Peixoto, T. C. [UNESP] (Springer, 2020)
We study the prospects of using femtoscopic low-momentum correlationmeasurements at the Large Hadron Collider to access properties of the J/psi-nucleon interaction. The QCD multipole expansion in terms of the J/psi chromopolarizability relates the forward scattering amplitude to a key matrix element to the origin of the nucleon mass problem, the average chromoelectric gluon distribution in the nucleon. We use information on the J/psi-nucleon interaction provided by lattice QCD simulations and phenomenological models to compute J/psi-nucleon correlation functions. The computed correlation functions show clear sensitivity to the interaction, in particular to the J/psi chromopolarizability.